Improving Activity and Learning Outcomes of Students by Using Quantum Teaching Learning Method - Nuria Advianti Rahayu (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2016)
The purpose of the research to know the using of Quantum Teaching model can increase the students’ activities and to know the using of Quantum Teaching model can increase the students learning outcomes The kind of the research is PTK with quantitative approach. The subjects of the research are students of class VIIB at MTs Walisongo 3 Banyuanyar. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method thet used qualititif and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: Quantum Teaching, students activity, and learning outcome